ANALISIS STRUKTUR DAN PERILAKU EKONOMI UNTUK MENENTUKAN SEKTOR PEREKONOMIAN UNGGULAN DI PROPINSI JAWA TIMUR - M. Rondhi (University of Jember, 2009)
The aim of the research were to study the economic structure and performance in East Java, and to find the main sector to be improved in East Java. The data was collected from BPS especially input-output data. So the analysis tools that used in this research are backward and forward linkage analysis, output and income multiplier effect.From the structure aspect shows that the high backward linkage sectors are paper industry textile, clothes sector, oil mills industry sector, resort and hotel industry sector, food industry sector, cigarette and beverage sector, construction sectors. Furthermore, that high forward linkage sectors are paper industry textile, clothes sector, cigarette, food and beverage sector, resort and hotel sector, trading, transportation and communication sector. Furthermore, based on the performance aspect, the high output multiplier sectors are paper industry textile, clothes sectors, oil mills industry, resort and hotel industry sector, food industry sector, cigarette and beverage sector, construction sectors. In other side the high income multiplier sectors are public government and security, paper, textile, clothes sector, forestry sector, paddy sector and other foods sector. Finally, the main sectors to be improved in East Java are paper, textile, clothes sector, resort and hotel, cigarette, food and beverage sector and construction sector.Keywords: Structure and conduct of economic sectors, Multiplier effect, Backward and Forward linkage